(untitled) (Global Journal of Science Frontier Research, 2012)
Semiannual variations of the geomagnetic disturbances for different geomagnetic activity indices exhibit distinct characteristics for the period of 1970-2009. In this paper, the semiannual variation of geomagnetic activity is significant in the low-latitudinal Dst index showing the magnitude of the ring current, less significant in the midlatitude of Ap and Kp indices. There is no evidence of semiannual variation in the auroral electrojet AE index but clearly observed in AL index which are measure of global geomagnetic activity in the auroral zone, also responds to convection electrojets and substorms electrojet. The correlation coefficient was used to determine the reliability of the variation, which ranges between 0.595-0.988.